Incorporation of Islamic principles to the land tenure system in west peninsular Malaysia: prospect and progress - Maidin, Ainul Jaria; Mobarak Ali, Bashiran Begum (LexisNexis, 2009)
It is undeniable that the early Malay land tenure system is a fusion between the Islamic principles and Malay customary law. However, with the advent of the colonial administration and introduction of the English common law into the Malay states legal system, brought about the eradication of the principles of Islamic law. Thus, Islamic law at present is largely limited to areas of personal matters only (marriage, divorce, custody of children and other matters within the exclusive jurisdiction of the Syariah Courts in Peninsular Malaysian States). This article seeks to examine the prospect and progress of Islamising of the Malaysian land law and the challenges within the system that is stultifying the process.